2012
DOI: 10.1371/journal.pone.0033237
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rapid DNA Microarray Assay Enables Identification of 37 Mycoplasma Species and Highlights Multiple Mycoplasma Infections

Abstract: Mycoplasmas comprise a conglomerate of pathogens and commensals occurring in humans and animals. The genus Mycoplasma alone contains more than 120 species at present, and new members are continuously being discovered. Therefore, it seems promising to use a single highly parallel detection assay rather than develop separate tests for each individual species. In this study, we have designed a DNA microarray carrying 70 oligonucleotide probes derived from the 23S rRNA gene and 86 probes from the tuf gene target r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…Rebelo et al (2011) reported a relatively rapid method that employed PCR amplification of ITS followed by high resolution melt analysis; however, this method only identified Mycoplasma and analysis is difficult. Recently, a matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry method for identification of ruminant Mycoplasma (Pereyre et al, 2013) and a rapid DNA microarray assay for identification of both Mycoplasma and Acholeplasma (Schnee et al, 2012) have been reported. However, both methods require specialized and expensive equipment, and the matrix-assisted laser desorption/ionization time-offlight mass spectrometry method is intended for a high density mycoplasma specimen, requiring additional culture.…”
Section: Discussionmentioning
confidence: 99%
“…Rebelo et al (2011) reported a relatively rapid method that employed PCR amplification of ITS followed by high resolution melt analysis; however, this method only identified Mycoplasma and analysis is difficult. Recently, a matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry method for identification of ruminant Mycoplasma (Pereyre et al, 2013) and a rapid DNA microarray assay for identification of both Mycoplasma and Acholeplasma (Schnee et al, 2012) have been reported. However, both methods require specialized and expensive equipment, and the matrix-assisted laser desorption/ionization time-offlight mass spectrometry method is intended for a high density mycoplasma specimen, requiring additional culture.…”
Section: Discussionmentioning
confidence: 99%
“…bovoculi was further verified in 14 and 18 randomly selected samples from herds 2 and 3, respectively, using a Mycoplasma spp. microarray assay (Schnee et al, 2012).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…(Schnee et al, 2012), 12/14 were positive for Myc. bovoculi and 1/14 was positive for Ureaplasma diversum.…”
Section: Sybr Green Real-time Pcr For Detection Of Mycoplasma Bovoculimentioning
confidence: 99%
“…One disadvantage of the PCR/ DGGE method is the cost of the specialised equipment and the specialist technical skills required to perform the test and analyse the results. As of yet, no other test has delivered similar sensitivity and flexibility in identifying and detecting a range of Mycoplasma species, although a microarray described by Schnee et al (19) may be the method of choice in the future.…”
Section: Discussionmentioning
confidence: 99%